2010
DOI: 10.1016/j.biortech.2010.03.101
|View full text |Cite
|
Sign up to set email alerts
|

The cost and effectiveness of solids thickening technologies for treating backwash and recovering nutrients from intensive aquaculture systems

Abstract: The cost and effectiveness of three solids thickening processes, i.e., gravity thickening settlers (GTS), inclined belt filters (IBF), geotextile bag filters (GBF), were individually evaluated with the biosolids backwash produced in intensive aquaculture systems equipped with microscreen drum filters and radial-flow settlers. The IBF produced the cleanest discharge and highest treatment efficiencies, likely reflecting the rapid efficiency with which solids are separated from wastewater. The GBF was the least e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
1
20
0
3
Order By: Relevance
“…Also, sludge in the SE units was 13 times more concentrated than that removed from the WE mainly due to compressibility inside the settler (Sharrer, Rishel, Taylor, Vinci & Summerfelt 2010). Total suspended solids (TSS) production was lower probably due to the lower P/R ratio and lower FCR observed in this treatment.…”
Section: Water Usementioning
confidence: 99%
“…Also, sludge in the SE units was 13 times more concentrated than that removed from the WE mainly due to compressibility inside the settler (Sharrer, Rishel, Taylor, Vinci & Summerfelt 2010). Total suspended solids (TSS) production was lower probably due to the lower P/R ratio and lower FCR observed in this treatment.…”
Section: Water Usementioning
confidence: 99%
“…However, the minimal water use associated with RAS technology concentrates wastes into (i) a solid waste/wastewater stream associated with solids settling/dewatering and (ii) an effluent stream. The waste/wastewater stream typically contains high concentrations of suspended solids and high biochemical oxygen demand (BOD) and chemical oxygen demand (COD) stemming from concentration and dewatering of fish manure and uneaten fish feed using technologies such as gravity thickening settlers or inclined belt filters (Sharrer et al, 2010). The effluent stream is generated from a small flushing or "exchange" flow that is added to the fish production system to help dilute the accumulation of nitrate (NO 3 -) in the fish tanks.…”
Section: Introductionmentioning
confidence: 99%
“…A simple integration of CTW into a recirculating hatchery was conducted by Buřič et al (Buřič et al, 2015) in the Czech Republic that different from traditional RASs which generally involve specialized technologies, such as microsieve filtration, ozonization, and UV sterilization (Azaizeh et al, 2013;Good et al, 2011;Sharrer et al, 2010;Terjesen et al, 2013). This study indicated that CTW integration has the potential to increase production (potential final biomass with CW use was estimated to be 40% greater than without CW use) of a recirculating hatchery without added operational or environmental costs.…”
Section: Constructed Treatment Wetlands Invoked For Effluent Treatmentmentioning
confidence: 98%